INCORRECT SURGICAL TACTICS IN BLEPHAROPTOSIS: CONSEQUENCES AND COMPLICATIONS - Munirakhon S. Kasimova ,; Mufazzalkhon M. Iminova , (Central Asian Journal of Medicine, 2025)
The correction of upper eyelid ptosis is one of the most common surgeries performed by oculoplastic surgeons, and recently by plastic surgeons as well. However, even the most experienced specialists note that the results are not always satisfactory. Successful outcomes are primarily achieved when performing levator aponeurosis surgery, with various authors reporting success rates between 70% and 95%. Among patients seeking consultation at the oculoplastic surgery department of the Republican Clinical Ophthalmology Hospital (RCOH) of the Ministry of Health of the Republic of Uzbekistan, upper eyelid ptosis accounts for 18-22% of cases in various years[5,6].